RESIDENT TREATMENT THROUGH ISLAMIC GUIDENCE WITH DAYAH-BASED - Linur Ficca Agustina; Afni Damanik (Ash-Shudur : Jurnal Bimbingan dan Konseling Islam, 2021)
Dayah-based Islamic guidance for handling residents at the Atjeh Peduli Foundation cares for the City of Lhokseumawe. with the aim of knowing Islamic guidance, effectiveness and obstacles faced at the Atjeh Care Foundation in Lhokseumawe City in implementing Islamic guidance based on dayah. This type of research is qualitative with a field study approach. Collecting data using interviews, observation and documentation. Descriptive qualitative data analysis technique. The results of the study are that: (1) Islamic guidance based on dayah is carried out in several parts: a) the time and schedule of guidance is carried out four times a week. The implementation time starts some after the Maghrib prayer and some after the Insha prayer it ranges from 2 hours to 3 hours, and b) activities or guidance materials include: Sufism material, tahlil, worship practices, our yellow recitation, c) the Islamic guidance method based on dayah is carried out with dengan al-hikmah, al-mau’idzah, al-mujadalah bi al latihiyah ahsan. (2) It has not been fully felt effective, because there are still residents whose new guidance has not been able to provide changes in their behavior. (3) The obstacles faced are: a) the patient is closed to his condition, b) unstable and changeable behavior and attitudes, c) feeling healed or recovered, d) patients who think they do not need rehabilitation, e) families are less able to cooperate.